Unlocking the black box of plant biostimulants - du Jardin, Patrick; Brown, Patrick H.; DeJong, Theodore M.; Cassán, Fabricio; Ferrante, Antonio; Fotopoulos, Vasileios; Manganaris, George A.; Carillo, Petronia (My University, 2025)
Over the recent years, plant biostimulants have shifted from the margins of agricultural innovation to the forefront of global discussions towards sustainable crop production models. Despite their growing popularity and commercial relevance, key questions persist regarding their actual effects on plants, the validation of their claimed benefits, and the identification of reliable metrics to assess their impact. This editorial aspires to navigate through the definitions, scientific evidence, and regulatory frameworks shaping the current and future landscape of biostimulants. Building on this foundation, the present article reflects on the broader scientific discussion initiated during the ISHS HortForum on plant biostimulants, aiming to distil key conceptual and methodological challenges in the field. An integrated perspective on how biostimulants can be more effectively studied, functionally categorized, and applied in modern agriculture from a range of perspectives is discussed. This analysis provides a critical synthesis of current scientific thinking. It highlights key research priorities, particularly concerning mechanisms of action, quantifiable effects, and the role of biostimulants in promoting resilient, sustainable cropping systems.